Professional Agent Perspectives on Representing WNBA Athletes in the United States - Gomez-Joseph, Rosemond; Gioia, Joseph A; Lanza, Kerry; Berger, Michael; Domingo, Aldwin (Archives of Business Research, 2024)
The purpose of this qualitative phenomenological study was to explore the experiences, challenges, and opportunities faced by professional sports agents in the United States who represent professional Women’s National Basketball Association (WNBA) athletes. Data were collected using semi-structured interviews with 15 professional sports agents. A thematic analysis of the data helped identify 11 major themes which included (a)Contract items negotiated, (b)WNBA’s contract negotiations differences from other professional leagues, (c)Contract negotiation Challenges, (d)Level of Branding and Marketing involvement of Professional agents, (e)Brand and marketing challenges, (f)Marketing and branding WNBA athletes versus other professional leagues athletes, (g)Branding and marketing opportunities, (h)Experiences with client management, (i)Career needs assessment for WNBA athletes , (j)Client Management Challenges, and (k)Career transition Opportunities for WNBA athletes (i.e. retirement). The study findings have implications for professional sports agents and best practices.